Flocculation of Clay Colloids Induced by Model Polyelectrolytes: Effects of Relative Charge Density and Size. Issue 19 (2nd August 2017) - Sakhawoth, Yasine; Michot, Laurent J.; Levitz, Pierre; Malikova, Natalie
Abstract: Flocculation and its tuning are of utmost importance in the optimization of several industrial protocols in areas such as purification of waste water and civil engineering. Herein, we studied the polyelectrolyte‐induced flocculation of clay colloids on a model system consisting of purified clay colloids of well‐defined size fractions and ionene polyelectrolytes presenting regular and tunable chain charge density. To characterize ionene‐induced clay flocculation, we turned to the combination of light absorbance (turbidity) and ζ‐potential measurements, as well as adsorption isotherms. Our model system allowed us to identify the exact ratio of positive and negative charges in clay–ionene mixtures, the (c+/c−) ratio. For all samples studied, the onset of efficient flocculation occurred consistently at c+/c− ratios significantly below 1, which indicated the formation of highly ionene‐deficient aggregates. At the same time, the ζ‐potential measurements indicated an apparent zero charge on such aggregates. Thus, the ζ‐potential values could not provide the stoichiometry inside the clay–ionene aggregates. The early onset of flocculation in clay–ionene mixtures is reminiscent of the behavior of multivalent salts and contrasts that of monovalent salts, for which a large excess amount of ions is necessary to achieve flocculation. Clear differences in the flocculation behavior are visible as a function of the ionene charge density, which governs the conformation of the ionene chains on the clay surface. Abstract : Flocculation of colloidal platelets by oppositely charged polyelectrolyte chains is studied on a clay–ionene model system, with an emphasis on the relative charge density and relative size of the two components. Clear differences in the flocculation behavior are visible as a function of the ionene charge density, which governs the conformation of the ionene chains on the clay surface.